1963
DOI: 10.1677/joe.0.0260085
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 5-Hydroxytryptamine on Pregnancy

Abstract: The action of 5-hydroxytryptamine (5-HT) on pregnancy in mice has been investigated. Deleterious effects have been observed at all stages. In advanced pregnancy a single dose may kill the foetuses within half an hour.The effect in early pregnancy can be antagonized by progesterone and by prolactin, as can the toxic effects of the drug on the experimental decidual reaction. In late pregnancy progesterone produces little, and prolactin no, reversal of the toxic action of 5-HT. It is suggested that in early pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

1964
1964
1987
1987

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…The levels of 5HT in the placenta and foetus after treatment of the mother with several monoamine oxidase inhibitors were measured, and found to show no significant increase above the normal levels in these tissues. Treatment with cyproheptadine, a SHT antagonist, did not delay parturition.Previous work has shown that both 5-hydroxytryptamine (5HT) and monoamine oxidase inhibitors will interrupt pregnancy in mice if administered during the early stages (Lindsay, Poulson & Robson, 1963). This action can be prevented if progesterone or prolactin is given concurrently with these drugs, which suggests that in some way luteal secretion is inhibited and that this is responsible for the interruption of pregnancy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of 5HT in the placenta and foetus after treatment of the mother with several monoamine oxidase inhibitors were measured, and found to show no significant increase above the normal levels in these tissues. Treatment with cyproheptadine, a SHT antagonist, did not delay parturition.Previous work has shown that both 5-hydroxytryptamine (5HT) and monoamine oxidase inhibitors will interrupt pregnancy in mice if administered during the early stages (Lindsay, Poulson & Robson, 1963). This action can be prevented if progesterone or prolactin is given concurrently with these drugs, which suggests that in some way luteal secretion is inhibited and that this is responsible for the interruption of pregnancy.…”
mentioning
confidence: 99%
“…5HT was used as the creatinine sulphate (May & Baker), the dose administered being 40 mg/kg of the salt, subcutaneously. All assay results are given in terms of the base.The doses of monoamine oxidase inhibitors were based on those used in previous experiments on pregnancy (Poulson & Robson, 1963). Doses of iproniazid are ix terms of the phosphate, two different doses being administered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the first half of pregnancy the effect occurs when the drug is given daily for several days, e.g. from the first to sixth day, and appears to be due to an interference with the hormonal mechanism responsible for the maintenance of gestation (Lindsay, Poulson & Robson, 1963).…”
Section: Introductionmentioning
confidence: 99%
“…In the first half of pregnancy the effect occurs when the drug is given daily for several days, e.g. from the first to sixth day, and appears to be due to an interference with the hormonal mechanism responsible for the maintenance of gestation (Lindsay, Poulson & Robson, 1963).In the second half of pregnancy the effect of 5-HT comes on very rapidly 718 J. M. ROBSON AND F. M. SULLIVAN and usually causes death of the foetuses within 0-5 hr following a single injection (Poulson, Botros & Robson, 1960). It seemed likely at first that this was due to a direct toxic effect of the drug on the foetus, but this was found not to be so.…”
mentioning
confidence: 99%